"Estágio Profissional: um lugar de desafios e aprendizagens" - Ana Isabel Castro Mendes de Queirós Vaz (2019)
The Professional Internship is inserted in the second year of Masters on Physical Education teaching in elementary and secondary school, in Faculty of Sports, University of Porto. It is characterized by the conclusion of the initial formation of the future Physical Education teacher, where are offered conditions in order to the profession can be practiced and learned in practical situations inside the school reality. This document refers to the Internship Report made by an internship student and it describes the experiences that were lived during her year of Professional Internship. The Internship Report is structured in five big chapters. In the first - Introduction - it is mirrored the goals of this document. In the second - Personal Framework - a "trip" is made to internship student's past as a propulsor of the future, allowing the understanding of the path taken until the realization of the profession of Physical Education's teacher. Also in this chapter, there is a reference to her expectations for this year, confronting then with the reality that was lived. The third chapter - Professional Practice Framework - describes the legal and institutional framework of Professional Internship and the understanding of the school, and all the elements that took part of this year are characterized: the cooperative school, the disciplinary group of Physical Education, the internship core, the cooperative teacher, the adviser teacher, the resident class and the shared class. The Realization of the Professional Practice is the chapter that refers to all the experiences lived during the year, which had been written based in what was lived and felt. It was always based on a critical and detailed reflection of what should be the practice of pedagogical teaching. In the fifth and final chapter - Conclusion and Future Perspectives - it is made a final balance about the Professional Internship and it's given some perspectives about the future in this teaching area.